An analysis of students ability in writing descriptive text at the tenth grade students of vicational high school negeri 4 lubuklinggau: An analysis of students ability in writing descriptive text at the tenth grade students of vicational high school negeri 4 lubuklinggau - Perizon Ansori (LIED: Lingustic, Literature and English Education, 2022)
ABSTRACT The problem in this research was How was the tenth grade students ability in writing descriptive text at the SMKN 4 Lubuklinggau? The objective of this research was to find out an analysis of students ability in writing descriptive text at the tenth grade students of SMKN 4 Lubuklinggau. The descriptive used quantitative method and the data collected through the writing descriptive text. The population of this research was 25 students of the tenth grade students of SMKN4 Lubuklinggau. The sample of this research was 25 students who taken from one class by using random sampling. Based on the result of the writing descriptive text at the tenth grade students of SMKN 4 Lubuklinggau was in passed category the mean score was 65,00. The students for Excellent were 13 students or 52%. The students for Good 9 were students or 36%. The students for Weak were 3 students or 12%. The students for poor were 0 students or 0% in writing descriptive text. It means that the students in this research had passed in the writing descriptive text at SMKN 4 Lubuklinggau.KeyWords: Students Ability, Writing Descriptive Text